Spinoza and relational autonomy : being with others - Armstrong, Aurelia; Green, Keith; Sangiacomo, Andrea, 1986- (Edinburgh University Press, 2019)
This collection of 13 new essays shows what Baruch Spinoza can add to our understanding of the relational nature of autonomy. By offering a relational understanding of the nature of individuals centred on the role played by emotions, Spinoza offers not only historical roots for contemporary debates but also broadens the current discussion.